Evaluating pre-analytical sample error in haematology laboratory at a tertiary care teaching hospital in Nepal - Dev Kumar Sah, Surya; Prasad Sharma G, Ram; Ray Yadav, Sanjay (Journal of Chitwan Medical College, 2026)
Introduction: The pre-analytical phase, from test ordering to sample processing, is significantly affected by sample errors and impacts the accuracy of haematology laboratory results. The majority of errors occur during this period, which affects diagnosis and patient care. This study aims to recognise prevalent pre-analytical sample errors occurring in the haematology laboratory and reduce these errors, possibly improving the quality management systems. Method: A cross-sectional descriptive study was conducted in the haematology laboratory of Chitwan Medical College and Teaching Hospital, Nepal, using data collected from September 2024 to August 2025. Data sources included the laboratory information system and handwritten registers. Pre-analytical errors assessed included haemolysis, clotted samples, missing identification, delayed transport, and insufficient samples. Descriptive statistical analysis of error frequencies and percentages was performed using IBM SPSS version 21. Result: Out of 100,995 samples analysed, 2,037 (2.0%) exhibited pre‑analytical errors. Within these errors, the haematology central laboratory accounted for the majority with 1,519 (74.6%), while the emergency laboratory accounted for 518 (25.4%). Insufficient sample volume and haemolysis were identified as the most common types of pre-analytical errors. Conclusion: he most common pre-analytical errors in the haematology laboratory were insufficient sample volume and haemolysis. Ongoing staff training, implementation of automated systems, adherence to standard operating procedures, and compliance with quality standards are essential for improving laboratory efficiency, diagnostic accuracy, and patient safety.